Holocene re‐colonisation, central–marginal distribution and habitat specialisation shape population genetic patterns within an Atlantic European grass species. (22nd December 2014) - Harter, D. E. V.; Jentsch, A.; Durka, W.; Wang, X.‐Q.
Abstract Corynephorus canescens (L.) P.Beauv. is an outbreeding, short‐lived and wind‐dispersed grass species, highly specialised on scattered and disturbance‐dependent habitats of open sandy sites. Its distribution ranges from the Iberian Peninsula over Atlantic regions of Western and Central Europe, but excludes the two other classical European glacial refuge regions on the Apennine and Balkan Peninsulas. To investigate genetic patterns of this uncommon combination of ecological and biogeographic species characteristics, we analysed AFLP variation among 49 populations throughout the European distribution range, expecting (i) patterns of SW European glacial refugia and post‐glacial expansion to the NE; (ii) decreasing genetic diversity from central to marginal populations; and (iii) interacting effects of high gene flow and disturbance‐driven genetic drift. Decreasing genetic diversity from SW to NE and distinct gene pool clustering imply refugia on the Iberian Peninsula and in western France, from where range expansion originated towards the NE. High genetic diversity within and moderate genetic differentiation among populations, and a significant pattern of isolation‐by‐distance indicate a gene flow drift equilibrium within C. canescens, probably due to its restriction to scattered and dynamic habitats and limited dispersal distances. These features, as well as the re‐colonisation history, were found to affect genetic diversity gradients from central to marginal populations. Our study emphasises the need for including the specific ecology into analyses of species (re–)colonisation histories and range centre–margin analyses. To account for discontinuous distributions, new indices of marginality were tested for their suitability in studies of centre–periphery gradients.